Experimental and computational electrochemistry of quinazolinespirohexadienone molecular switches – differential electrochromic vs photochromic behavior - Webb, Eric W.; Moerdyk, Jonathan P.; Sluiter, Kyndra B.; Pollock, Benjamin J.; Speelman, Amy L.; Lynch, Eugene J.; Polik, William F.; Gillmore, Jason G. (Beilstein Journal of Organic Chemistry, 2019)
Our undergraduate research group has long focused on the preparation and investigation of electron-deficient analogs of the perimidinespirohexadienone (PSHD) family of photochromic molecular switches for potential application as "photochromic photooxidants" for gating sensitivity to photoinduced charge transfer. We previously reported the photochemistry of two closely related and more reducible quinazolinespirohexadienones (QSHDs), wherein the naphthalene of the PSHD is replaced with a quinoline. In the present work, we report our investigation of the electrochemistry of these asymmetric QSHDs. In addition to the short wavelength and photochromic long-wavelength isomers, we have found that a second, distinct long-wavelength isomer is produced electrochemically. This different long-wavelength isomer arises from a difference in the regiochemistry of spirocyclic ring-opening. The structures of both long-wavelength isomers were ascertained by cyclic voltammetry and 1H NMR analyses, in concert with computational modeling. These results are compared to those for the symmetric parent PSHD, which due to symmetry possesses only a single possible regioisomer upon either electrochemical or photochemical ring-opening. Density functional theory calculations of bond lengths, bond orders, and molecular orbitals allow the rationalization of this differential photochromic vs electrochromic behavior of the QSHDs.
Keywords: cyclic voltammetry; density functional theory; heterocycles; molecular switches; photochromic photooxidants; spirocycles

Organic Photochromic and Thermochromic Compounds - Crano, J. C.; Guglielmetti, R. J. (Plenum Press, 1999)

Photochromism: Molecules and Systems, revised ed. - Duerr, H.; Bouas-Laurent, H. (Elsevier, 2003)

Proceedings of the fourth International Symposium on Photochromism Photoswitchable Molecular Systems and Devices - Desvergne, J.-P.; Pozzo, J.-L. (Mol. Cryst. Liq. Cryst., 2005)

Organic Photoswitchable Multifunctional Molecules and Materials - Branda, N.; Tian, H. (Dyes Pigm., 2011)

Special issue on Photochromism 1 and 2 - Favaro, G.; Irie, M. (J. Photochem. Photobiol., C, 2011)

Electrochromism and Electrochromic Devices - Monk, P. M. S.; Mortimer, R. J.; Rosseinsky, D. R. (Cambridge University Press, 2007)
and references therein.

U.S. Pat. Appl. - Baumann, K. L.; Lin, R.; Giri, P.; Franz, S. (Protic-Soluble Organic Electrochromic Compounds, 2017)

(untitled) - Jarosz, T.; Gebka, K.; Stolarczyk, A.; Domagala, W. (Polymers (Basel, Switz.), 2019)
and references therein.

(untitled) - Madasamy, K.; Velayutham, D.; Suryanarayanan, V.; Kathiresan, M.; Ho, K.-C. (J. Mater. Chem. C, 2019)

Organic Photochromic and Thermochromic Compounds - Minkin, V. I.; Komissarov, V. N.; Kharlanov, V. A. (Perimidinespirocyclohexadienones, 1999)
and references therein.

(untitled) - Gillmore, J. G.; Neiser, J. D.; McManus, K. A.; Roh, Y.; Dombrowski, G. W.; Brown, T. G.; Dinnocenzo, J. P.; Farid, S.; Robello, D. R. (Macromolecules, 2005)

(untitled) - Kavarnos, G. J.; Turro, N. J. (Chem. Rev., 1986)
and references therein.

(untitled) - Borsub, N.; Kutal, C. (J. Am. Chem. Soc., 1984)

(untitled) - Evans, T. R.; Wake, R. W.; Sifain, M. M. (Tetrahedron Lett., 1973)

(untitled) - Hasegawa, E.; Okada, K.; Ikeda, H.; Yamashita, Y.; Mukai, T. (J. Org. Chem., 1991)

Advances in Electron Transfer Chemistry - Bauld, N. L. (Hole and electron transfer catalyzed pericyclic reactions, 1992)
and references therein.

(untitled) - Bauld, N. L.; Gao, D.; Aplin, J. T. (J. Phys. Org. Chem., 1999)

(untitled) - Bauld, N. L.; Gao, D. (Polym. Int., 2000)

(untitled) - Bauld, N. L.; Roh, Y. (Tetrahedron Lett., 2001)

(untitled) - Roh, Y.; Gao, D.; Bauld, N. L. (Adv. Synth. Catal., 2001)

(untitled) - Moerdyk, J. P.; Speelman, A. L.; Kuper, K. E., III; Heiberger, B. R.; Ter Louw, R. P.; Zeller, D. J.; Radler, A. J.; Gillmore, J. G. (J. Photochem. Photobiol., A, 2009)

(untitled) - Lynch, E. J.; Speelman, A. L.; Curry, B. A.; Murillo, C. S.; Gillmore, J. G. (J. Org. Chem., 2012)

(untitled) - Pavlishchuk, V. V.; Addison, A. W. (Inorg. Chim. Acta, 2000)

(untitled) - Barachevsky, V. A.; Butenko, V. G. (Russ. J. Gen. Chem., 2018)

Gaussian 03, Revision D.01 (Gaussian, Inc., 2004)

Curie Cluster

MU3C – Midwest Undergraduate Computational Chemistry Consortium

(untitled) - Kuwata, K. T.; Kohen, D.; Krueger, B. P.; Polik, W. F. (Counc. Undergrad. Res. Quart., 2012)

Gaussian 09, Revision A.1 (Gaussian, Inc., 2009)

(untitled) - Roothaan, C. C. J. (Rev. Mod. Phys., 1960)

(untitled) - Becke, A. D. (J. Chem. Phys., 1996)

(untitled) - Becke, A. D. (Phys. Rev. A, 1988)

(untitled) - Lee, C.; Yang, W.; Parr, R. G. (Phys. Rev. B, 1988)

(untitled) - Hariharan, P. C.; Pople, J. A. (Theor. Chim. Acta, 1973)

(untitled) - Tomasi, J.; Mennucci, B.; Cammi, R. (Chem. Rev., 2005)